(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
الهدف من الدراسة: تهدف هذه الدراسة إلى تقييم فعالية العلاج الضوئي بالأشعة فوق البنفسجية ذات الحزمة الضيقة UVBnb المنفرد والمشارك مع الميتوتريكسات لدى مرضى الصداف اللويحي، ومقارنة الآثار الجانبية ومعدل النكس بين نوعي العلاج. نمط الدراسة: دراسة تجريبية عشوائية. الطرق: دراسة تجريبية عشوائية شملت 40 مريضاً مصاباً بالصداف، 16 مريضاً منهم تلقوا معالجة ضوئية UVBnb بالاضافة الى معالجة بالميتوتركسات، و 24 منهم تلقوا معالجة ضوئية فقط. تمت مراقبة جميع المرضى أثناء فترة العلاج بمقياس PASI كل أسبوعين، وبعد الشفاء كل 4 أسابيع، كما تمت مقارنة الآثار الجانبية بين طريقتي العلاج وقياس معدل النكس بعد الشفاء. النتائج: لم نلاحظ وجود فروق هامة إحصائيا بين مجموعتي العلاج الضوئي المنفرد والمشارك فيما يتعلق بالشفاء، حيث كان معدل الشفاء بالنسبة لمجموعة المشاركة 75% مقابل 46% لمجموعة العلاج الضوئي المنفرد، كان الاسمرار وفرط التصبغ أشيع أثرين جانبيين لكلا المجموعتين، كان معدل النكس 22.7% من مرضى الدراسة جميعهم كانوا من مجموعة العلاج الضوئي المنفرد. الخلاصة: في دراستنا تبين أن العلاج الضوئي المنفرد بUVB nb يمتلك فعالية مشابهة للعلاج المشارك مع الميتوتريكسات، وإن العلاج المشارك بالميتوتريكسات يقلل من عدد الجلسات العلاجية الضوئية UVBnb المطلوبة لتحقيق الشفاء. الآثار الجانبية لطريقتي العلاج متحملة من قبل المريض. يحدث النكس أكثر مع العلاج الضوئي المنفرد. Objectives: This study aims to assess the efficacy of UVBnb phototherapy alone, and with methotrexate in plaque psoriasis, and comparing the side effects and relapse between the two kinds of treatments. Study Design: randomized experimental study. Methods: A total of 40 psoriasis patients were included in the study, 16 patients were treated with UVBnb and methotrexate, whereas 24 patients were treated with UVBnb alone. PASI was calculated for every patient every 2 weeks through treatment, and every 4 weeks after clearance. Side effects and relapse were compared between two kinds of therapy. Results: there were no statistical important differences between two groups of study according to clearance, clearance rate in combination group was 75% vs. 46% in phototherapy group, tanning and hyperpigmentation were the most common side effects for both groups, recurrence rate was 22.7% in study patients, all of them were from phototherapy group. Conclusion: this study revealed that UVBnb phototherapy alone,and with methotrexate have the same efficacy in the treatment of psoriasis, and the combined therapy with methotrexate reduce the number of UVBnb treatments necessary for clearance. Side effects were tolerated in both kinds of treatments. Relapse after clearance occurs more likely with alone UVBnb phototherapy.